Effects of tDCS of Dorsolateral Prefrontal Cortex on Dual-Task Performance Involving Manual Dexterity and Cognitive Task in Healthy Older Adults - Ljubisavljevic, Milos R.; Oommen, Joji; Filipovic, Sasa; Bjekic, Jovana; Szolics, Miklos; Nagelkerke, Nico (Frontiers in Aging Neuroscience, 2019)
Healthy aging limits the activities of daily living and personal independence. Furthermore, cognitive-motor interference in dual-task (e.g., walking while talking) appears to be more pronounced in the elderly. Transcranial direct current stimulation (tDCS), a form of the non-invasive brain stimulation technique, is known to modify cortical excitability and has been investigated as a tool for enhancing learning in health and disease. The present study examined the effects of the dorsolateral prefrontal cortex (DLPFC), applied while dual-tasking (on-line), improves performance in healthy older humans. Anodal, cathodal, bilateral or sham tDCS targeting left DLPFC was applied while performing the grooved pegboard test (GPT) and serial seven subtraction test (SSST) alone or together (dual-tasking). The number of pegs and the number of correct subtractions were recorded before, during and 30 minutes after tDCS. The dual-task performance was measured as the percent change from single to the dual-task condition (dual-task cost DTC). Only bilateral, anode left tDCS, induced a significant increase in subtracted numbers while dual-tasking, i.e., it reduced the DTC of manual dexterity (GPT) to a cognitive task. Significant changes 30 minutes after the stimulation were only present after bilateral anode right tDCS on GPT dual-task costs. These findings suggest that anodal tDCS applied online interacts with a dual-task performance involving demanding cognitive and manual dexterity tasks. The results support the potential use of non-invasive brain stimulation for improvement of cognitive functioning in daily activities in older individuals.